ROS-Induced DCTPP1 Upregulation Contributes to Cisplatin Resistance in Ovarian Cancer - Wang, Yu; Chen, Peishi; Chen, Xueping; Gong, Daoyuan; Wu, Yingsong; Huang, Liping; Chen, Yao (Frontiers in Molecular Biosciences, 2022)
Cisplatin resistance hinders the improvement of the prognosis of patients with ovarian cancer. Cisplatin induces cancer cell apoptosis by inducing reactive oxygen species (ROS). dCTP pyrophosphatase 1 (DCTPP1) is a newly discovered dNTP pyrophosphatase.This study aimed to identify the role of DCTPP1 in oxidative stress and cisplatin response of ovarian cancer.Our results indicates cisplatin-induced ROS generation was responsible for the upregulation of DCTPP1 in ovarian cancer cells, whereas DCTPP1 knockdown significantly enhanced the sensitivity of ovarian cancer cells to cisplatin,reflect in reactive oxygen species (ROS) generation, double-strand DNA breaks, and cell apoptosis. The expression of redox-related genes and the activation of the PI3/AKT signaling pathway were also inhibited by DCTPP1 knockdown.Our data proposes that the development of therapeutic approaches targeting DCTPP1 may be useful in the treatment of ovarian cancer.